Study on the composition of fish species in Thu Bon - Vu Gia river, Quang Nam province - Phuong Anh, Vu Thi; Phu, Vo Van (Academia Journal of Biology, 2012)
Species’s composition of the fishes in Thu Bon - Vu Gia river, Quang Nam province is quite biodiversity. Our surveys, that were carried out from 2005 - 2009, have revealed that there are 197 species belonging to 121 genus, 48 families and 15 orders, among which, the Cypriniformes is the one being the most plentiful with 82 species reaching (41.62%). The Cyprinidae reaching 69 species, Belontidae reaching 9 species, Balitoridae reaching 8 species, Gobiidae reaching 8 species, Eleotridae reaching 7 species, Mugilidae reaching 6 species, Cobitidae reaching 5 species, Terapontidae reaching 5 species, are dominant about species. Dominating species’s composition of Cypriniformes in regional fauna showing the typical fresh water’s quality. Among 197 species in Thu Bon - Vu Gia, there were 8 valuable and rare species marked in the Red Book of Viet Nam (2007), 7 species are classified as level VU (Vulnerable) - will be endangered and 1 species are classified as level EN (Endangered) should be protected